Sustainability – a new dimension in information systems evaluation - Piotrowicz, W; Cuthbertson, R (Emerald, 2009)
The paper introduces new dimensions of Information Systems evaluation. Sustainability issues have increasing importance and their influence is compared with the Internet revolution. Customers, policymakers and business partners increasingly require the monitoring and reporting of the impact of an organisation on sustainability. However, traditional IS evaluation approaches are not able to capture the impact of IT/IS on sustainability, especially in relation to social and environmental dimensions. In order to stimulate discussion and research, the authors propose a framework that was originally developed to focus on supply chain practices. The framework is built upon three dimensions: economic, social and environmental, which are divided further into three sub-dimensions. It can be used as a staring point to develop a framework for sustainability-oriented IS evaluation. In the paper the sustainability drivers are presented, and the problems related to IT/IS evaluation are discussed using selected examples from IT/IS applications in supply chains. IT/IS solutions used in supply chains are perceived as having both positive and negative effects on sustainability. Moreover some business models supported by IT/IS that are perceived as positive for the supply chain processes, could be considered negative after taking into consideration their external effects on sustainability. Sustainability and its new dimensions create new challenges for Information Systems evaluation. Companies require frameworks and tools that can help to measure and evaluate the organisational impact on sustainability, to create a sustainability-oriented IS evaluation. The researcher’s role is to answer such needs and concentrate on this emerging research topic.